ТАВАНТОЛГОЙН ОРДЫН O, III, IV, IX ДАВХРААСУУДЫН НҮҮРСНИЙ ПЕТРОГРАФИЙН НАЙРЛАГА, ХҮЛЭР ХУРИМТЛАЛЫН ҮЕИЙН ФААЦЫН НӨХЦӨЛ - Л., Жаргал (Geological Issues, 2021)
Middle Permian Tavantolgoi coal deposit is located in SouthGovi Basin. The deposit is the largest coal deposit in Mongolia and has 16 coal seams. Petrographic studies indicate that coals of seam O, III, IV and IX were clarain, duroclarain, clarodurain and durain microlitotypes. Organic materials were mostly formed from wood of trunks, roots and leaves. Predominant inorganic matters in coal were clay, silica, carbonate and sulfide minerals. Based on the results of petrographic and mineral composition analyses, peat-forming condition was reconstructed as stagnant forest swamp with fluctuated groundwater level for the lower seams and stagnant forest swamp with running water for upper seams.